Mathematical correlation in the mathematics book for the first intermediate grade in Iraq (Journal of the College of Basic Education, 2022)
The recent of research aims at identifying the mathematical coorelation in the Iraqi Textbooks for the Intermediate Stage in Iraqi.This comes out by answering on the following questions:What is the rate of mathematical Coorelation in the Prescribed Mathematical Textbooks for the Students at the ( First, Second, and third) Classes and among them.The researcher Followed the descriptive and analytic investigation. She Prepares many question standing For the mathematical coorelation classifies in the Following aspects:(Mathematical Cognitive Coorelative Components, Mathematical Conceptions representation Coorelations,The relationship among the mathematical topics, Other uses of Mathematics in other Fields, Uses of Mathematics in life and daily life Situation, Viewing Mathematics as a whole, Problem solving in Mathematics and the application of Mathematical and Patterming, Evaluating the role of Mathematics in the culture and society). Data were Collected and analyzed. Then Computed by the Following statistical tools ( Alpha Chronback, The weighted average, Centennial weight). The findings of the study are as follows:The rate of Mathematical Coorelation in the Mathematical textbooks is %55 at the first stage textbooks whereas it is %53 at the second stage textbooks and %48 at the third stage textbooks and the rate among them is %156.And in the Light of what is Presented the researcher put Forwards some Conculsions:There is a Correlation in the contents of each textbook but it is shown that the rate is weak.The interest is Considerable for the textbooks designers in the Components of the first-stage intermediate due to the criteria of the Mathematical Correlation.Some recommendations are put forward:The teachers guide should be supplied to erery teacher having the mathematical criterio.The textbooks ddesigners should be practiced on content analysis according to the mathematical correlation.And some suggestions are sunbmitted:To take the Mathematical Correlation in to Consideration as one of Mathematical Principles for the Educational studies and Future researches.To vary the Components of the Mathematical issues in the Intermediate textbooks stage due to the Mathematical Integration.